Canadian missionaries, Angolan protestants, and the PIDE: research sources - Luce, Frank J. (Africana Studia, 2020)
The text which follows involves the interpretation of an anonymous report found in the PIDE fonds at the Torre do Tombo National Archive in Lisbon. The method is to analyse the context in which the report was written and to corroborate the facts alleged in the report through reference to independent sources. The contextual analysis is in two parts: first, a general synopsis of the Protestant mission which is the subject matter of the report; and second, the life story of the report’s putative author. The substance of the report is then deconstructed with regard to its circumstances, content, and purpose. Keywords: Angola, PIDE, protestant, missionary, interpretation.